Makna Simbolis Tari Kembang Ura Dalam Tradisi Topeng Sidakarya: Kajian Etnoestetika - Dewa Ayu Galih Mas Narapadi Galih; Ni Made Ruastiti; Kompiang Gede Widnyana (Pusat Penerbitan LPPM Institut Seni Indonesia Bali, 2026)
Kembang Ura Dance is a newly created dance work that emerges from the reinterpretation of the flower-scattering ritual found in the Sidakarya Mask performance, an essential ritual practice within the Balinese Hindu ceremonial system. In the context of contemporary performing arts, the transformation of ritual actions into aesthetic forms often entails the risk of meaning reduction and the profanation of sacred symbols. This condition generates an urgency to examine how ritual values can be translated into choreographic works without losing their cultural and spiritual depth. This study aims to reveal the symbolic meanings of Kembang Ura Dance through an ethno-aesthetic perspective, focusing on its performance structure, the process of transforming the flower-scattering tradition, and the symbolic meanings embedded in its artistic elements. The research addresses three main questions: how the aesthetic structure of Kembang Ura Dance is constructed, how the flower-scattering tradition is transformed into a creative dance form, and what symbolic meanings are articulated within the cultural context of Sidakarya. Employing a qualitative method with ethno-aesthetic and ethnochoreological approaches, data were collected through performance observation, in-depth interviews, and documentation studies. The analysis is supported by ethno-aesthetic theory, ritual theory, and symbolic perspectives in performance studies. The findings indicate that Kembang Ura Dance does not merely represent aesthetic movement but also articulates symbols of purification, universal compassion, and ritual blessing through its choreographic structure, vintage-inspired costume design, and its symbolic relationship with the Sidakarya Mask as the ritual completer of yadnya. The novelty of this study lies in positioning Kembang Ura Dance as a model of ritual-based creative dance that maintains a balance between modern aesthetics and the continuity of sacred values, while offering a critical reading of the role of creative dance within contemporary Balinese cultural dynamics. Keywords: Kembang Ura Dance; symbolic meaning; ethno-aesthetics; flower-scattering tradition; Sidakarya Mask.